Penerapan teknologi tepat guna pompa air tenaga angin untuk sirkulasi air di kolam ikan - Edi Suhardi Rahman; Dyah Vitaloka; Jumadi M. Parenreng (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This training aims to improve the production offishing industry, increase the availability of fresh fishes, aswell as to decrease the fish deaths. Method used in thistraining were discussion and question and answer session,which were used to test the water of participants’ the generalknowledge on circulation technology; lecture method was usedto share the theory on water circulation and appropriatetechnology; hands-on practice activity was used to guide theparticipants in maintenance wind water pump circulating watertechnology; and evaluation method was used to see whetherthe technology is functioned well and fixing bugs if there isany. The outcome targets of this training are to make the freshwater fish cultivators educated and able to make as well as toimplement the appropriate technology for their sustainablebusiness; to share information about appropriate technology onwater circulation and clean water management increase salesin order to meet the high fish needs of the community; tocooperate with street vendors (pecel lele stall, fish traders) andcatering; has the ability to maintain water ponds and cleanwater management to increase fish yield in order to increasebusiness income and meet household needs; can developbusiness by opening freshwater fish farming land that has theright technology to circulate water. The results of this trainingshow that construction of appropriate technology for watercirculation can increase the fish production, reduce the numberof fish deaths above 70%, form the marketing prospects forfish products to be sold at markets, suppliers and food stalls,add skills and knowledge, and encourage freshwater fishfarming groups to increase their income.